State Capacity in Russia, Past and Present: A Commentary on Yanni Kotsonis, States of Obligation: Taxes and Citizenship in the Russian Empire and Early Soviet Republic - Chandler, Andrea (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2016)
The author provides a commentary on Yanni Kotsonis, States of Obligation: Taxes and Citizenship in the Russian Empire and the Early Soviet Republic. Many of the challenges of pre-revolutionary taxation, as identified by Kotsonis, continue to exist even today in Putin’s Russia. The country’s large size, unwieldy state and the precarious basis of individual rights continue to make it difficult to establish a cohesive taxation system. At the same time, taxation is dynamic and contested in many states, precisely because it is difficult to balance the complexity of modern taxation with the fair treatment that citizens expect to receive from their state.